The A3 adenosine receptor (A3AR): therapeutic target and predictive biological marker in rheumatoid arthritis. Issue 9 (September 2016) - Fishman, Pnina; Cohen, Shira
Abstract The Gi protein-associated A3 adenosine receptor (A3 AR) is over-expressed in inflammatory cells, and this high expression is also reflected in the peripheral blood mononuclear cells of patients with autoimmune inflammatory diseases such as rheumatoid arthritis, psoriasis, and Crohn's disease. CF101, a selective agonist with high affinity to the A3 AR, is known to induce robust anti-inflammatory effect in experimental animal models of adjuvant-, collagen-, and tropomyosin-induced arthritis. The effect is mediated via a definitive molecular mechanism entailing deregulation of the nuclear factor-κB (NF-κB) and the Wnt signal transduction pathways resulting in apoptosis of inflammatory cells. CF101 was found to be safe and well tolerated in all preclinical, phase I, and phase II human clinical studies. In two phase II clinical studies where CF101 was administered to rheumatoid arthritis (RA) patients as a stand-alone drug, a significant anti-rheumatic effect and a direct significant correlation were found between receptor expression at baseline and patients' response to the drug, suggesting that A3 AR may be utilized as a predictive biomarker. The A3 AR is a promising therapeutic target in rheumatoid arthritis and can be used also as a biological marker to predict patients' response to CF101. This is a unique type of a personalized medicine approach which may pave the way for a safe and efficacious treatment for this patient population.